The Aesthetic Movement 1869-1890 : Catalogue of an exhibition at the Camden Arts Centre London 15 August - 7 October 1973. - Spencer, Charles (Londen : Academy Editions, 1973)
Catalogue of an exhibition at the Camden Arts Centre London 15 August - 7 October 1973
Adlib record nr. 530000742
kunstcatalogus
Keywords: aesthetic movement